Peran Komite Dalam Meningkatkan Mutu Sekolah Di MI Ma’arif 03 Limbangan Cilacap - Sarno Hanipudin; Zulaekha Zulaekha (Al-Fikr: Jurnal Pendidikan Islam, 2020)
The role of the committee in improving the quality of education is that it is able to assist and coordinate with the school in order to continuously improve quality through the four roles it plays. With the establishment of good communication between the school and the school committee on how to improve the quality of schools, the facilities and infrastructure that support each Madrasah performance in improving quality will be realized. This research was conducted with the aim of describing the role of the School Committee in the effort to improve the quality at MI Ma'arif 03 Limbangan Cilacap. The aspects studied included the role of the School Committee as a provider of consideration, supporter, controller, and mediator. This study uses a qualitative approach and the type of research is Field Research. Data collection uses observation, interview, and documentation techniques. The instrument used was the researcher himself. The research subjects were the principal and the school committee. The object of the research was the role of the school committee in improving the quality of education. The data analysis process was carried out by data classification, data reduction, data presentation, and data verification. The technique of checking the validity of the data used triangulation of sources and methods.